Farelo de acerola em programa de restrição alimentar para suínos pesados - Castelini, Fabrício Rogerio [UNESP] (2015)
Two experiments were conducted to evaluate the use of acerola meal in feeding programs for heavy pigs. In the first experiment we used 16 pigs in two treatments (basal diet-BD and test diet-TD with the addition of 30% acerola meal) and eight replicates. In the second experiment we used 48 pigs, with initial weight of 78.81 ± 5.10 and 123.42 ± end of 10.76 kg, allocated in a randomized block design with four dietary treatments (basal diet -BD and inclusions increasing 9 - AC9, 18 - and 27% AC18 - AC27 acerola meal) and 12 repetitions. The high level NDF (76.47%), ADF (63.78%), cellulose (45.90%) and hemicellulose (12.69%) of acerola meal, resulted in reductions of their digestible nutrients, and linear decreases in their digestibility. During the second experiment, the animals in linear decreases (p<0.0001) of the daily weight gain, daily digestible energy intake and decreasing feed conversion. Comparing the carcasses of animals that received the basal diet fed with the AC27, there were 23.65% reduction in the average back fat thickness and 39.84% fat area, having, however, increases the 10.44% in the percentage of lean-meat. The qualitative characteristics of meat were not affected by meal levels evaluated acerola meal. Reductions in the levels of Myristic and Palmitic fatty acids and increases in the levels α linolenic and linoleic conjugate. The largest fiber contents acerola promoted increases in the excretion residues and reduction in the biogas potential (54.55%) and methane (55.56%) per kilogram of in natura feces. Economic indicators were also affected making it impossible to profit in the short term